P23 Associate Principal Investigators in Trauma Trials. (8th April 2021) - Bretherton, Chris; Exell, Lauren; Achten, Juul; Costa, Matt; Bretherton, Chris
Abstract: Oxford Trauma has designed a collection of randomised clinical trials to answer important clinical questions in trauma and meaningfully engage trainees and associate principal investigators (aPI's) with research. These include: Children's Radius Acute Fracture Fixation Trial (CRAFFT): Weight-Bearing in Ankle Fractures (WAX): Blood cEll Salvage and autoTransfusion (BEST): Fractured Ankle Management Evaluation (FAME): Surgery or Cast for Injuries of the EpicoNdyle in Children's Elbows (SCIENCE): The HUmeral SHaft fracture trial (HUSH) Trainee engagement is promoted via: Registration for the NIHR associate PI scheme with corresponding "how-to guide" for study set-up. Individually tailored points system for collaborative authorship. Automatic emailing of certificates for recruitment of participants (For ARCP evidence). A central database listing trial sites and contacts for aPI's. https://www.ndorms.ox.ac.uk/Oxford-Trauma-and-Emergency-Care/trainee-involvement This has led to the recruitment of sites and participants ahead of target, including sites aPI's have set-up from scratch. We would love for you to join as an aPI or help us refine the model and share it with other collaborative groups!: Contact Christopher.Bretherton@ndorms.ox.ac.uk